METAPSIKOSIS TUHAN DALAM LOKALITAS KETUHANAN BALI : KAJIAN TEKS TUTUR GONG BESI - Harsananda, Hari; Wayan Gaduh, Acyutananda Wayan Gaduh (Pangkaja: Jurnal Agama Hindu, 2026)
This research explores the local Balinese theological dimensions contained in the Tutur Gong Besi text. Utilizing a qualitative approach with a hermeneutic framework, this study aims to identify the distinctive characteristics of Balinese Theology that differentiate it from normative or mainstream Hindu theology. The primary finding of this research is the concept of "metapsychosis of God," where Bhatara Dalêm, as the supreme divine entity, is not transcendent-static but continuously moves and manifests in 21 different loci—ranging from sacred spaces like temples to profane spaces like kitchen utensils—under various identities and titles. This concept is deeply rooted in an animistic substrate shaped by Balinese agrarian culture. Furthermore, the text reveals a cyclic eschatological construction that positions heaven—rather than moksa—as the temporary destination of the soul before undergoing rebirth (punarbhawa) after a 21-year period. The findings confirm that Balinese Theology is an autonomous, distinctive, and authentic theological system born from the ecological and historical context of Balinese society.